Phase‐modulation based dual‐function radar‐communications. Issue 8 (1st October 2016) - Hassanien, Aboulnasr; Amin, Moeness G.; Zhang, Yimin D.; Ahmad, Fauzia
Abstract : The authors develop a novel phase‐modulation based dual‐function system with joint radar and communication platforms. A bank of transmit beamforming weight vectors is designed such that they form the same transmit power radiation patterns, whereas the phase associated with each transmit beam towards the intended communication directions belongs to a certain phase constellation. During each radar pulse, a binary sequence is mapped into one point of the constellation which, in turn, is embedded into the radar emission by selecting the transmit weight vectors associated with that constellation point. The communication receiver detects the phase of the received signal and uses it to decode the embedded binary sequence. The proposed technique allows information delivery to the intended communication receiver regardless of whether it is located in the sidelobe region or within the main radar beam. Three signalling strategies are proposed which can be used to achieve coherent communications, non‐coherent communications, and non‐coherent broadcasting, respectively. It is verified that the proposed method provides improved bit error performance as compared to previously reported sidelobe modulation based dual‐functionality techniques.